The cultural beliefs of the Vhavenda on the causes and transmission of sexually transmitted infections - Fhumulani Mavis Mulaudzi (AOSIS, 2007)
Cultural and ethnic identity and folk beliefs play a decisive role in perceptions, attitudes and practices regarding health care and illness. Opsomming Kulturele en etniese identiteit en volksgelowe speel 'n deurslaggewende rol in die persepsies, houdings en gebruike ten opsigte van gesondheidsorg en siekte. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.